DINAMIKA DERAJAT PERSAINGAN INDUSTRI PERBANKAN INDONESIA - Zuhroh, Idah (Faculty of Economics and Business, University of Muhammadiyah Malang, 2014)
This study aims to investigate the dynamics of the degree of competition in the banking industry in Indonesia, especially in the banking consolidation period ( 2000 -2008) is measured from the concentration ratio (CR 8) and Learner index. Samples were grouped into eight largest bank size (CR8) and outside CR8. The findings indicate that during the consolidation period (2000 -2006), concentration ratio tend to decrease of 70% towards 62%. But after periode 2006, concentration index is constan. Degree of competition by largest bank size (CR8) indicated by an Learner index greater and is likely to increase rather than smaller bank size (outside CR 8). This gives a signal that largest bank size have more market power to direct output prices ( credit ) above marginal cost compared to the group of banks outside of CR 8.